ENLARGEMENT OF SCLEROCHOROIDAL CALCIFICATIONS: MULTIMODAL IMAGING UPDATE - Slean, Geraldine R. (Retin Cases Brief Rep, 2018)
PURPOSE: To report the multimodal imaging and enlargement of sclerochoroidal calcifications over a 10-year period. METHODS: Case report of a 74-year-old white man who presented for routine follow-up and was found to have yellow chorioretinal lesions in the right eye. RESULTS: Multimodal imaging was performed and confirmed sclerochoroidal calcifications. Comparison of fundus photography over a 10-year period demonstrated growth of preexisting lesions and the development of new lesions in the right eye. CONCLUSION: Over time, this patient developed new sclerochoroidal calcifications and enlargement of preexisting calcifications. We, therefore, recommend regular follow-up with periodic multimodal imaging for these patients.